PENGARUH PENAMBAHAN KALSIUM ASETAT (Ca(CH3COO)2) DAN BIOETANOL TERHADAP KARAKTERISTIK BIOETANOL GEL - Adriani Purba, Arnita; Admadi, Bambang; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret, 2017)
This study aims to 1) knowing the effect of calcium acetate and ethanol to the characteristics of bioethanol gel, 2) knowing the adding of calcium acetate and ethanol which gives the best characteristics of bioethanol gel. This study uses a randomized block design factorial design. The first factor is the addition of calcium acetate which consists of four levels: 15 grams, 20 grams, 25 grams, 30 grams and the second factor is bioethanol, which consists of three levels: 75 grams, 85 grams and 95 grams. Variables observed were how long it lasts, viscosity, calorific value, thermal efficiency, the percentage of combustion residue, ash content. The addition of calcium acetate and ethanol concentration and their interactions very significant effect on the characteristics of bioethanol gel. Bioethanol gel with the addition of calcium asetate 20 grams and bioethanol 85 grams of bioethanol with the best treatment that has long lit 3,380 s / g, viscosity 6200 cPa.s, calorific value 4610,596 kJ/kg, the thermal efficiency of 0.47, the percentage of combustion residues 0269%, and % ash content 0.0892. The keyword : calcium asetate, bioethanol, bioethanol gel .
Keywords: 135